The Causa of Johannes Falkenberg and Synodal Praxis at the Council of Constance (1414–1418): Between Council and Pope - Provvidente, Sebastian (2022)
While the council fathers at the Council of Constance (1414–1418) managed toachieve a specific condemnation of the theses of Wyclif, Hus. and Jerome of Prague, in thecase of Jean Petit, the council only made a very general judgement of tyrannicide through thedecree Quilibet tyrannus. Something similar occurred with some of the theses of JohannesFalkenberg as, even though its author was imprisoned and his theses were condemned asseditious, they were not expressly condemned as heretical by the council, giving rise tostrenuous complaints from representatives of the Polish crown to Pope Martin V, who madea protest at the last session of the council claiming that the case had not been properlydecided and presenting an appellatio ad futurum concilium. This article analyzes the disputeover the theses of Johannes Falkenberg at the Council of Constance, focusing on the debatesthat took place within the natio gallicana. It also attempts to explain the correlation betweenthe consolidation of conciliar authority and the course of the Falkenberg case.